Combined Visualization and Heat Transfer Measurements for Steam Flow Condensation in Hydrophilic and Hydrophobic Mini-Gaps - Chen, Xi; Derby, Melanie M. (My University, 2016)
Condensation enhancement was investigated for flow condensation in mini-channels. Simultaneous flow visualization and heat transfer experiments were conducted in 0.952-mm diameter mini-gaps. An open loop steam apparatus was constructed for a mass flux range of 50–100 kg/m2s and steam quality range of 0.2–0.8, and validated with single-phase experiments. Filmwise condensation was observed in the hydrophilic mini-gap; pressure drop and heat transfer coefficients were compared to the (Kim and Mudawar, 2013, “Universal Approach to Predicting Heat Transfer Coefficient for Condensing Mini/Micro-Channel Flow,” Int. J. Heat Mass Transfer, 56(1–2), pp. 238–250) correlation and prediction was very good; the mean absolute error (MAE) was 20.2%. Dropwise condensation was observed in the hydrophobic mini-gap, and periodic cycles of droplet nucleation, coalescence, and departure were found at all mass fluxes. Snapshots of six typical sweeping cycles were presented, including integrated flow visualization quantitative and qualitative results combined with heat transfer coefficients. With a fixed average steam quality (x¯ = 0.42), increasing mass flux from 50 to 75 to 100 kg/m2s consequently reduced average sweeping periods from 28 to 23 to 17 ms and reduced droplet departure diameters from 13.7 to 12.9 to 10.3 μm, respectively. For these cases, condensation heat transfer coefficients increased from 154,700 to 176,500 to 194,800 W/m2 K at mass fluxes of 50, 75, and 100 kg/m2 s, respectively. Increased mass fluxes and steam quality reduced sweeping periods and droplet departure diameters, thereby reducing liquid thickness and increasing heat transfer coefficients.
Citation: Chen X, Derby MM. Combined Visualization and Heat Transfer Measurements for Steam Flow Condensation in Hydrophilic and Hydrophobic Mini-Gaps. ASME. J. Heat Transfer. 2016;138(9):091503-091503-11. doi:10.1115/1.4033496.